2013
DOI: 10.1111/coa.12106
|View full text |Cite
|
Sign up to set email alerts
|

A 2013 updated systematic review & meta‐analysis of 36 randomized controlled trials; no apparent effects of non steroidal anti‐inflammatory agents on the risk of bleeding after tonsillectomy

Abstract: Background Although the literature suggests that non‐steroidal anti‐inflammatory drugs (NSAIDs) are effective in controlling post‐operative pain in the paediatric population, physicians have been reluctant to utilise these medications after tonsillectomy due to concerns of increased bleeding rates. While many surgeons prescribe opioid analgesics postoperatively, these are associated with a number of potential adverse side‐effects including nausea, vomiting, constipation, excessive sedation and respiratory comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(115 citation statements)
references
References 68 publications
6
97
0
8
Order By: Relevance
“…[6][7][8][9][10] In a 2003 study by Marrett, the preoperative use of NSAIDs was associated with increased risk of reoperation for hemostasis versus those who received placebo or narcotic. 6 A study by Møiniche that same year found that postoperative NSAID use leads to increased likelihood of having a PTH requiring reoperation.…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8][9][10] In a 2003 study by Marrett, the preoperative use of NSAIDs was associated with increased risk of reoperation for hemostasis versus those who received placebo or narcotic. 6 A study by Møiniche that same year found that postoperative NSAID use leads to increased likelihood of having a PTH requiring reoperation.…”
Section: Methodsmentioning
confidence: 99%
“…An slightly increase of reoperation has been confirmed in a recent review, while results of another recent review consider NSAIDs safe not only because does not increase bleeding and secondary haemorrhage but does not influence the need of reoperation [121,122] . Two studies evaluating perioperative blood loss during preoperative administration of diclofenac and ibuprofen after hip arthroplasty and hip replacement have been discordant because an increase of 45% and 32% of blood loss [122,123]. In contrast, a recent study of Friedman et al have shown no increased risk of bleeding also when non-steroidal anti-inflammatory drugs or aspirin is associated to dabigratan in patients undergone to hip or total knee arthroplasty [124].…”
Section: Postoperative Bleedingmentioning
confidence: 84%
“…In a study of patients undergoing tonsillectomy, an increase of number of reoperation but not an increase in bleeding has been observed with a number needed to treat of 60 [120]. An slightly increase of reoperation has been confirmed in a recent review, while results of another recent review consider NSAIDs safe not only because does not increase bleeding and secondary haemorrhage but does not influence the need of reoperation [121,122] . Two studies evaluating perioperative blood loss during preoperative administration of diclofenac and ibuprofen after hip arthroplasty and hip replacement have been discordant because an increase of 45% and 32% of blood loss [122,123].…”
Section: Postoperative Bleedingmentioning
confidence: 92%
“…Les inquiétudes concernant l'augmentation de la survenue d'hémorragies lors de l'usage des AINS à la suite d'une amygdalectomie relèvent de leur mécanisme d'action. En effet, les AINS inhibent de façon réversible les cyclo-oxygénases, ce qui diminue la production de prostaglandines et cause une réduction de l'agrégation plaquettaire 7 . Les enfants qui sont sous l'effet des AINS subissent une légère augmentation de la durée de la coagulation, qui reste néanmoins dans les limites de la normale 18 .…”
Section: Types D'erreursunclassified
“…Les choix d'analgésiques pouvant être utilisés pour les enfants après une chirurgie en otorhino-laryngologie sont controversés. Les anti-inflammatoires non stéroïdiens (AINS) sont peu utilisés en raison des risques potentiels de saignements liés à leur activité antiplaquettaire 7 . Les effets indésirables liés aux opiacés peuvent en limiter l'usage chez pour les enfants.…”
Section: Introductionunclassified